Mobile and georeferenced electromagnetic sensors and applications for salinity assessment - Urdanoz, V.; Amezketa Lizarraga, E.; Clavería, I.; Ochoa, V.; Aragües Lafarga, R. (Spanish Journal of Agricultural Research, 2008)
Soil salinity is a major threat in irrigated agriculture because of its negative on-site (decreased productivity) and off-site (salinization of irrigation return flows) effects. The delineation of the spatial variability of soil salinity is best suited using non-invasive geophysical measurements of the apparent soil electrical conductivity (ECa) using mobile GPS-based systems. Two simple and cost-effective Mobile Georeferenced Electromagnetic Sensors (MGES) developed in Aragón and Navarra (Spain) are described. These devices involve electromagnetic instruments towed by all terrain vehicles and combined with GPS units and data acquisition systems that collect both ECa readings and GPS coordinates. Two applications of the MGES aimed at delineating ECa maps for (1) selecting the most suitable crops in a 43-ha saline site (Hondo de Espartosa) and (2) correlating ECa with drainage water salinity to ascertain the salinity-source areas in a new 715 ha irrigated basin (Barranco de Lerma) were examined. These examples demonstrate the MGES surveying capacities for management of salt-affected agricultural areas.